The effect of economic inequality on young children's prosocial decision‐making. (12th April 2020) - Kirkland, Kelly; Jetten, Jolanda; Nielsen, Mark
Abstract : An emerging body of literature has documented the negative implications high economic inequality can have on children's social and cognitive development. However, little experimental research has directly addressed how wealth discrepancies impact the way children treat others. The current study thus aimed to address the implications of economic inequality on prosocial decision‐making in children prior to commencing formal schooling. Using a novel experimental paradigm, we immersed 4‐year‐old children ( N  = 58) in a series of games where they played against puppets for rewards. During this process, children were exposed to resource allocations featuring either high inequality or low inequality. We subsequently measured children's donation behaviour, resource division behaviour, and fairness perceptions. As predicted, children were less altruistic when exposed to high inequality compared to low inequality. Contrary to predictions, there was no difference in resource division behaviour or fairness perceptions. This study documents for the first time that exposure to environmental inequality, even if brief and in a controlled experimental setting, can influence young children's prosocial decision‐making. Statement of contribution What is already known on the subject? Adults tend to be less prosocial towards others after experiencing high economic inequality. Young children understand when outcomes are unequal. Young children also have a rudimentary understanding of what is fair. What does this study adds? A novel experimental design was utilized to immerse children in a safe experimental economy. Pre‐schoolers are less altruistic after experiencing high inequality compared to low inequality. Children did not attempt to adjust prior inequalities in their resource division behaviour.